2016
DOI: 10.1074/jbc.m115.709675
|View full text |Cite
|
Sign up to set email alerts
|

Exon Skipping in the RET Gene Encodes Novel Isoforms That Differentially Regulate RET Protein Signal Transduction

Abstract: Rearranged during transfection (RET), a receptor tyrosine kinase that is activated by the glial cell line-derived neurotrophic factor family ligands (GFLs), plays a crucial role in the development and function of the nervous system and additionally is required for kidney development and spermatogenesis. RET encodes a transmembrane receptor that is 20 exons long and produces two known protein isoforms differing in C-terminal amino acid composition, referred to as RET9 and RET51. Studies of human pheochromocytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In addition, cell membrane and receptor were also enriched in Figure 3B . For instance, Ret is a crucial gene that plays an important role in the development and function of the nervous system ( Gabreski et al, 2016 ), as well as driving HSCs survival. Ablation of Ret cannot only impair the number of HSCs but also influences its normal differentiation potential ( Fonseca-Pereira et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell membrane and receptor were also enriched in Figure 3B . For instance, Ret is a crucial gene that plays an important role in the development and function of the nervous system ( Gabreski et al, 2016 ), as well as driving HSCs survival. Ablation of Ret cannot only impair the number of HSCs but also influences its normal differentiation potential ( Fonseca-Pereira et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Others attempt to estimate junctions de novo from short reads ( Trapnell et al 2009 ; Dobin et al 2013 ; Kim et al 2013a ). The literature indicates that the vast majority of novel isoforms are assembled from currently annotated exons ( Booms et al 1999 ; Hide et al 2001 ; Zhou et al 2010 ; Lim et al 2011 ; Eswaran et al 2013 ; Kim et al 2013b ; Gabreski et al 2016 ; Nellore et al 2016 ; Tardaguila et al 2018 ). By designing a junction catalog that includes junctions created from all possible logical combinations of existing exons, and mapping to that catalog more true novel junctions are mapped than by mapping to the genome with a splice aware aligner.…”
Section: Discussionmentioning
confidence: 99%
“…Nellore et al ( Nellore et al 2016 ) studied more than 20,000 human RNA-seq samples derived from multiple cell types and found that that only 3.5% of junctions are not derivable in from existing genome annotations in some form, and that 81.4% are from already annotated transcripts. We also note that in the literature, there are examples of identified novel transcripts of several genes that are comprised of new combinations of known splice sites, frequently those that are the result of a variant inducing an exon-skipping event ( Booms et al 1999 ; Hide et al 2001 ; Zhou et al 2010 ; Lim et al 2011 ; Eswaran et al 2013 ; Kim et al 2013b ; Gabreski et al 2016 ). This suggests that an augmented reference consisting of probable new events based on the set of existing transcripts can be developed.…”
Section: Introductionmentioning
confidence: 96%
“…The third isoform of RET, RET43, was described in humans (Carter et al, 2001). Recently, two additional functional isoforms of RET that lack either exon 3 or exons 3–5 were described in CNS (Gabreski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%